2021
DOI: 10.1016/j.eats.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Single-Row Repair in Chronic Medial Collateral Ligament Insufficiency

Abstract: Medial collateral ligament (MCL) is the most commonly injured ligament of the knee. Acute Grade III MCL injuries can be managed conservatively except bony avulsion, intra-articular entrapment and Stener lesion, which requires surgical treatment by repair with or without augmentation. Chronic MCL injuries are treated surgically with various reconstruction techniques that are well established in the literature, which requires use of autograft or allograft and multiple tunnel placement with multiple implants for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Mukesh et al found that for MCL injury of proximal or distal side, single-row anchor repairing can achieve good results. is technique reattaches the torn ligament at its near anatomical attachment site using a single, double-loaded 5.5-mm suture anchor [22]. e present study suggests that repair of over-released MCL with suture anchors accompanied by utilization of unconstrained posterior stabilizing prosthesis in primary TKA is an adequate treatment strategy that avoids complications, improves long-term survivorship, and decreases bony resection without a constrained implant.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Mukesh et al found that for MCL injury of proximal or distal side, single-row anchor repairing can achieve good results. is technique reattaches the torn ligament at its near anatomical attachment site using a single, double-loaded 5.5-mm suture anchor [22]. e present study suggests that repair of over-released MCL with suture anchors accompanied by utilization of unconstrained posterior stabilizing prosthesis in primary TKA is an adequate treatment strategy that avoids complications, improves long-term survivorship, and decreases bony resection without a constrained implant.…”
Section: Discussionmentioning
confidence: 67%
“…Mukesh et al found that for MCL injury of proximal or distal side, single-row anchor repairing can achieve good results. This technique reattaches the torn ligament at its near anatomical attachment site using a single, double-loaded 5.5-mm suture anchor [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple surgical techniques purport to reproduce “normal anatomy” even though there is debate about the MCL bony attachments. 10 , 11 , 12 , 13 Several groups have recently described techniques that address the external rotation role of the dMCL. 14 , 15 , 16 The authors prefer a short isometric reconstruction construct because it is stiffer and resists valgus and axial rotation.…”
mentioning
confidence: 99%